Effect of digital tools in outpatient cardiac rehabilitation including home training—results of the EPICURE study - Hayn, Dieter; Sareban, Mahdi; Höfer, Stefan; Wiesmüller, Fabian; Mayr, Karl; Mürzl, Norbert; Porodko, Michael; Puelacher, Christoph; Moser, Lisa-Marie; Philippi, Marco; Traninger, Heimo; Niebauer, Josef (Frontiers in Digital Health, 2023)
Introduction Cardiovascular diseases are the leading cause of death worldwide and are partly caused by modifiable risk factors. Cardiac rehabilitation addresses several of these modifiable risk factors, such as physical inactivity and reduced exercise capacity. However, despite its proven short-term merits, long-term adherence to healthy lifestyle changes is disappointing. With regards to exercise training, it has been shown that rehabilitation supplemented by a) home-based exercise training and b) supportive digital tools can improve adherence. Methods In our multi-center study (ClincalTrials.gov Identifier: NCT04458727), we analyzed the effect of supportive digital tools like digital diaries and/or wearables such as smart watches, activity trackers, etc. on exercise capacity during cardiac rehabilitation. Patients after completion of phase III out-patient cardiac rehabilitation, which included a 3 to 6-months lasting home-training phase, were recruited in five cardiac rehabilitation centers in Austria. Retrospective rehabilitation data were analyzed, and additional data were generated via patient questionnaires. Results 107 patients who did not use supportive tools and 50 patients using supportive tools were recruited. Already prior to phase III rehabilitation, patients with supportive tools showed higher exercise capacity (Pmax = 186 ± 53 W) as compared to patients without supportive tools (142 ± 41 W, p < 0.001). Both groups improved their Pmax, significantly during phase III rehabilitation, and despite higher baseline Pmax of patients with supportive tools their Pmax improved significantly more (ΔPmax = 19 ± 18 W) than patients without supportive tools (ΔPmax = 9 ± 17 W, p < 0.005). However, after adjusting for baseline differences, the difference in ΔPmax did no longer reach statistical significance. Discussion Therefore, our data did not support the hypothesis that the additional use of digital tools like digital diaries and/or wearables during home training leads to further improvement in Pmax during and after phase III cardiac rehabilitation. Further studies with larger sample size, follow-up examinations and a randomized, controlled design are required to assess merits of digital interventions during cardiac rehabilitation.